Evaluating the compatibality of MS-Excel spreadsheet as an alternative data source in active server pages environment / Ali Seman - Seman, Ali (2006)
The use of the database as a data source has been seen as a phenomenal growth on the Internet. The web-to-database integration is often synonymously with web-based applications to be more dynamic and interactive in manipulating the contents. However, there are limitations in the adoption of database as the essential data source. The limitations are due to report productions, which are in the forms of tables and graphs. The tabular report requires data from many tables to be extracted from, where the graph needs a get-ready-component to populate the data through it. Moreover, the implementation of MS-Excel through web heading has its advantages of being online as well as sharing the resources all over the world. Besides that, the user can also manipulate the data locally and do it offline before putting it back to the web in order to be online. This research is to evaluate the compatibility of MS-Excel in manipulating the data through the common roles of the database such as inserting, viewing, updating and deleting the data, as well as to produce reports such as tabular reports, group reports and graphs reports. There were 26 test cases, which have been conducted to evaluate the compatibility of MS-Excel as an alternative data source. The overall results showed that MS-Excel was compatible to be an alternative data source. However, MS-Excel does not provide the data integrity constraint automatically like the database. Thus, it has to be controlled manually in order to utilize MS-Excel as a data source.